1362. Adding Insult to Injury: Association of Stigmatizing Language and Suboptimal Outcomes in People Who Inject Drugs. (4th December 2021) - Carpenter, Joseph; Catalanotti, Jillian S; Notis, Melissa; Brokus, Christopher J; Moran, Timothy P; Kuo, Irene; Akselrod, Hana; McGonigle, Keanan; Mai, William; Eaton, Ellen; Eaton, Ellen; Burgan, Kaylee W; et al.
Abstract: Background: The National Academy of Medicine has identified stigma surrounding substance use disorders (SUDs) and infectious diseases (ID) as a key barrier to integration of opioid use disorder (OUD) and ID services. Prior literature on stigmatizing language in OUD clinical care focuses on surveys and theoretical scenarios rather than real-world data. As part of a larger study of patients admitted for infectious complications of injection drug use (CHOICE), we sought to determine how inpatient physicians describe persons with OUD, as well as associations of this language with outcomes along the OUD continuum of care. Methods: CHOICE is a retrospective review of adults hospitalized with an infectious complication of OUD and IDU at four academic medical centers. Included patients were hospitalized between 1/1/2018-12/31/2018, had ICD9/10 diagnosis codes consistent with OUD and acute bacterial/fungal infection, and chart review verification of active infection associated with OUD. Data was abstracted regarding demographics, inpatient interventions, transitions of care, and outcomes 1 year after admission. Potentially stigmatizing language was identified based on the discharge summary. "Abuse" and "misuse" were considered potentially stigmatizing; "use disorder" was considered best practice. Associations of language and outcomes were analyzed via logistic generalized estimating equations. Results: A total of 287 subjects met inclusion criteria; 119 (42%) were female and the median age was 40 years (IQR: 32 – 52). The most common terms used to describe OUD were "abuse" (190, 66%) and "IVDU" (119, 42%). "Use disorder" was noted in only 72 (25%) charts. In a regression analysis, any mention of "use disorder" was associated with not leaving against medical advice (OR 2.48, 95% CI 1.24 – 4.95), a plan for ongoing OUD treatment (OR 5.17, 95% CI 2.05-13.0), and addiction-specific follow up (OR 2.94, 95% CI 2.34-3.68). Conclusion: In this multicenter retrospective study, inpatient physicians commonly referred to patients with OUD using stigmatizing language. When NIH-preferred language was used this was associated with improved outcomes along the OUD continuum of care, possibly reflecting increased awareness of best practices for treating patients with OUD. Disclosures: Ellen Eaton, MD, Gilead (Grant/Research Support) Ellen Eaton, MD, Gilead (Individual(s) Involved: Self): Research Grant or Support Greer A. Burkholder, MD, MSPH, Eli Lilly (Grant/Research Support) Sarah Kattakuzhy, MD, Gilead Sciences (Scientific Research Study Investigator, Research Grant or Support) Elana S. Rosenthal, MD, Gilead Sciences (Research Grant or Support)Merck (Research Grant or Support)